Odpowiedzi

  • Użytkownik Zadane
2009-09-06T15:15:59+02:00
(½)³÷(⅙)²-(-2)³=(⅛):(¹/₃₆)-(-8)=⅛*36+8=4,5+8=12,5
(-0,1)⁴ ×20³-(-2)⁴=0,0001*8000-16=8-16=8
(1½)³÷0,5⁴+7,4⁰=(³/₂)³:(½)⁴+1=²⁷/₄*16+1=109
5²×7²÷(2²+3)=25+49:(4+3)=25+49:7=25+7=32
(⅗)²-⅗²+⅗ ₂=⁹/₂₅-³/₂₅+³/₂₅=⁹/₂₅=0,36
Najlepsza Odpowiedź!
2009-09-06T15:20:13+02:00
(½)³÷(⅙)²-(-2)³= ⅛÷(1/36)-(-8) = ⅛*36+8 = 4,5+8 = 12,5
(-0,1)⁴ ×20³-(-2)⁴= 0,0001*8000-16 = 0,8 - 16 = -17,2
(1½)³÷0,5⁴+7,4⁰= (3/2)³÷ (1/16) + 1 = (27/8)*16+1 = 54+1=55
5²×7²÷(2²+3)= 25*49÷(4+3) = = 25*49÷7= 25*7 = 175
(⅗)²-⅗²+⅗ ₂= ⅗² = 9/25